Hepatocellular carcinoma in a non-B non-C non-alcoholic steatohepatitis (NBNC-NASH HCC) - M. F., Fairudz; Abdul Rahim, Noraini; J. M., Sharifah; Y., Rosna; Nordin, Abdul Jalil (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: Hepatocellular carcinoma (HCC) is the most common primary malignant liver tumour, which commonly occurs in those with underlying chronic liver problems mainly cirrhotic liver, with viral hepatitis (HBV and HCV) as the most common aetiological agent. HCC could also arise from non-cirrhotic liver, which include non-B non-C (NBNC) hepatitis, which is different in pathogenesis, epidemiology and prognosis. This disease entity would include the commonly benign fatty liver leading to non-alcoholic steatohepatitis (NASH) and HCC as sequelae. Methods: We present a case of non-B non-C HCC arising from a fatty liver in a non-alcoholic patient. Literature search was done with special emphasis on this disease. Conclusion: The incidence of NBNC HCC demonstrates an increasing trend, making it an important entity to be recognised early. A good understanding of this incidence would make it possible to predict the outcome, especially as me prognosis of non-B non-C HCC is fairly good if the HCC is found at an early stage.